PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMAN 1 PRAYA - Kariani Febrianti; Siti Nurmayanti; I Nyoman Nugraha Ardana Putra (Master of Management, Mataram University, 2023)
This study aims to determine whether the work environment and job satisfaction affect the performance of teachers at SMAN 1 Praya. The type of research used is associative research with a quantitative approach. The data collection method used is the census method. The population in this study were all teachers at SMAN 1 Praya. The number of samples used in this study were 86 teachers. The data collection technique used was documentation and distributing questionnaires containing statements about the work environment, job satisfaction and teacher performance. Questionnaires are used to get answers to the variables studied. The analytical tool used is multiple linear regression analysis using the SPSS 22 for windows program. The results of the data analysis show that: (1) the work environment has a positive and significant effect on teacher performance; (2) job satisfaction has a positive and significant effect on teacher performance. This means that implementing a comfortable work environment and feeling satisfied with the teacher will actually improve the performance of a teacher. Comfortable working conditions will make the teacher feel calm in doing his job well. Likewise, having a high sense of job satisfaction will make the teacher feel happy doing his work so that it will have an impact on the resulting performance.